(untitled) (Scientific journal of the Fergana State University, 2023)
The article explores the importance of studying and the heritage of our ancestors using a synergistic methodology. The author argues that this is of great importance for finding rational solutions to modern problems in the context of globalization. The article challenges the ideological interpretation of past research and suggests using modern philosophical methodology to better understand our identity. It also highlights the contribution of our ancestors to world civilization and the importance of educating young people about a rich historical past in order to create a sense of national pride. In addition, the article points to the significance of the philosophical views and discoveries of our great thinkers in the development of modern science. This article offers a valuable scientific and theoretical source for future research and progress.